Synergistic predictive value of MRI-based vertebral bone quality and CT hounsfield units for postoperative sagittal balance deterioration after cervical laminoplasty - Zheng, Bin; Yu, Panfeng; Zhu, Zhenqi; Liang, Yan; Liu, Haiying (Frontiers in Surgery, 2025)
BackgroundSagittal balance deterioration is major concern after cervical laminoplasty, which affects neurological recovery and quality of life. Preoperative bone quality may play a key role. CT-derived Hounsfield Unit (HU) values reflect bone mineral density, while MRI-derived vertebral bone quality (VBQ) values indicate bone marrow fat content. Their combined predictive value remains unclear.MethodsThis study retrospectively analyzes 104 patients (mean age 58.4 ± 11.6 years) who undergo posterior single-door laminoplasty with preoperative cervical CT and MRI. Mean HU and VBQ values (C2–T1) are measured, and patients are classified by postoperative change in cervical sagittal vertical axis (ΔcSVA). Logistic regression and ROC analyses are used to evaluate predictive performance.ResultsHU and VBQ differ significantly among improvement, stable, and deterioration groups (P < 0.001). Both HU (−0.007, P = 0.009) and VBQ (2.521, P = 0.018) independently predict postoperative imbalance. VBQ correlates negatively with HU (r = −0.306, P = 0.0016). ROC analysis shows AUCs of 0.690 for HU, 0.747 for VBQ, and 0.791 for the combined VBQ + HU model, with improved sensitivity (0.838) and specificity (0.597).ConclusionDecreased HU and elevated VBQ independently predict postoperative sagittal balance deterioration, reflecting complementary aspects of vertebral bone quality. The combined MRI- and CT-based assessment improves prediction accuracy and assists in preoperative risk stratification and individualized surgical planning.